2008
DOI: 10.1177/0363546508315201
|View full text |Cite
|
Sign up to set email alerts
|

Primary Repair of Ulnar Collateral Ligament Injuries of the Elbow in Young Athletes

Abstract: Primary repair of proximal and distal injuries of the medial ulnar collateral ligament is a viable alternative in the non-professional athlete. Graft reconstructions may not be necessary to obtain favorable outcomes and rapid return to sports in non-professional athletes who require surgical intervention for medial elbow instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 173 publications
(80 citation statements)
references
References 29 publications
3
73
0
4
Order By: Relevance
“…In the largest and most recent individual series, Savoie and co-investigators reported that 56/60 (93%) of players returned to the same or higher level of sport mostly within 6 months with 93% of patients achieving an excellent or good result according to the Andrews-Carson score [67]. There were six complications, two of which required return to the operating room all occurring in athletes who were able to return to sport.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In the largest and most recent individual series, Savoie and co-investigators reported that 56/60 (93%) of players returned to the same or higher level of sport mostly within 6 months with 93% of patients achieving an excellent or good result according to the Andrews-Carson score [67]. There were six complications, two of which required return to the operating room all occurring in athletes who were able to return to sport.…”
Section: Discussionmentioning
confidence: 98%
“…This procedure is currently indicated in young athletes with symptomatic instability of the elbow who have failed a course of non-operative management and have physical exam findings and radiographic evidence (stress X-rays and MR arthrogram) of valgus instability of the elbow due to MUCL deficiency [67]. Results have not been reported on professional athletes in recent series.…”
Section: Indications For Surgerymentioning
confidence: 99%
See 3 more Smart Citations